Reentrant phase transition of Born–Infeld-dilaton black holes - Seyed Hossein Hendi (European Physical Journal C: Particles and Fields, 2018)
Abstract We explore a novel reentrant phase transition of four-dimensional Born–Infeld-dilaton black hole in which the first order phase transition modify into a zeroth order phase transition below the critical point. Working in the extended phase space with regarding the cosmological constant as a pressure, we study the reentrant behavior of phase transition in the canonical ensemble. We show that these black holes enjoy a zeroth order intermediate-small black hole phase transition as well as a first order phase transition between small and large black holes for a narrow range of temperatures and pressures. We also find that the standard first order small–large black hole phase transition can modify into a zeroth order type. This zeroth order phase transition stands between the critical point and the first order phase transition region. We discuss the significant effect of the scalar field (dilaton) on the mentioned interesting treatment.